Descemet Membrane Endothelial Keratoplasty: Development of Contrast Sensitivity and Color Vision in Patients With Fuchs Endothelial Corneal Dystrophy. Issue 7 (July 2020) - Bayyoud, Tarek; Wilhelm, Helmut; Gelisken, Faik; Martus, Peter; Bartz-Schmidt, Karl Ulrich; Thaler, Sebastian
Abstract : Purpose: To assess the developments in contrast sensitivity, color vision, and subjective perception after Descemet membrane endothelial keratoplasty (DMEK) in patients with Fuchs endothelial corneal dystrophy (FECD). Methods: Included in this study were pseudophakic, unilateral DMEK patients with bilateral FECD having a follow-up period of 6 months (n = 23). The mean age at surgery was 70 years (range: 52–81 years). Pseudophakic eyes without history of other ocular pathology or surgery served as a control (n = 10). Pelli–Robson contrast sensitivity and Panel-D15 color vision tests were used. Best-corrected visual acuity, modified visual functioning questionnaire-25, central corneal thickness, and endothelial cell density were assessed. We visualized the subjective impression of patients with bilateral FECD after unilateral DMEK in a subgroup using Photoshop CS6. Results: Contrast sensitivity improved significantly from 1.35 ± 0.26 to 1.64 ± 0.17 ( P = 0.002; control eyes: 1.92 ± 0.09). No difference in the color vision error score was observed for preoperative and postoperative eyes ( P = 0.063). The best-corrected visual acuity improved significantly after surgery ( P = 0.001). The average values in the Logarithm of the Minimum Angle of Resolution were 0.59 ± 0.42 preoperatively and 0.1 ± 0.10 postoperatively (control eyes: 0.01 ± 0.03). Examinations revealed a decrease of the central corneal thickness and endothelial cell density after surgery ( P = 0.001; P = 0.001, respectively). Scores in the general and the driving questionnaire were significantly higher after surgery ( P = 0.001; P = 0.005, respectively). Conclusions: This study showed significant improvement in subjective patient satisfaction and contrast sensitivity. Spontaneous subjective color vision improvement might be explained by significantly improved contrast sensitivity. Contrast sensitivity might be considered as a parameter in preoperative decision-making and evaluation of surgical outcome. Abstract : Supplemental Digital Content is Available in the Text.